Clinical presentation and outcome in Acute Coronary Syndrome patients in relation to plaque morphology identified by Intra Vascular Ultra Sound - Mohammed Kamal Salama; Reda Biomy Bastawisy; Wael Anwar Haseeb (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate plaque morphology in non-culprit coronary arteries using intravascular ultrasound in patients with acute coronary syndrome with and without elevated glycated haemoglobin and its assocaition with patient outcome. Methods: The cross-sectional study was conducted at the Cardiology Department of Kafrelsheikh University, Egypt, from November 2019 to January 2022, and comprised adult patients of either gender suffering from acute coronary syndrome. The patients were divided into three groups. Diabetic patients were in group A, prediabetic patients with elevated glycated haemoglobin in group B, and patients with normal glycated haemoglobin in group C. The patients were subjected to coronary angiography and percutaneous coronary intervention. Intravascular ultrasound scan was done after succcessful intervention. Lesions were classified according to ultrasound findings. Patients were followed up for one year to observe subsequent events to the morphology of the lesions detected at baseline. Data was analysed using SPSS 20. Results: Of the 52 patients, 18(34.7%) were females and 34(65.3%) were males. Group A had 18(34.6%)patients; 13(72%) males and 5(28%) females with mean age 57.9±6.9 years. Group B had 17(32.7%) patients; 11(64.7%) males and 6(35.3%) females with mean age 56.5±5.5 years. Group C had 17(32.7%) patients; 10(59%) males and 7(41%) females with mean age 59.5±5.1 years (p>0.05). Thin-capped fibro-atheroma was significantly higher in groups A and B compared to group C (p=0.045). Significant direct correlation between major adverse cardiac events and prevalence of thin-capped fibro-atheroma was found between groups A and C (p=0.033), and between groups B and C (p=0.047) regarding prevalence of necrotic plaque and subsequent myocardial infarction. Conclusion: Thin-capped fibro-atheroma was the more common plaque type in patients with raised glycated haemoglobin, and the subsequent rate of major adverse cardiac events was significantly higher in such patients compared to the non-diabetic population. Keywords: Plaque, Atherosclerotic, Angiography, Vessels, Percutaneous, Prediabetic.